1979
DOI: 10.1148/133.3.769
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Positron Tomography with Manganese-52m

Abstract: The biodistribution of radiomanganese (54Mn) was studied in mice, rats, and dogs. Disappearance of radioactivity from the blood was extremely rapid, with a half-time of approximately 0.8 minutes. This resulted in very favorable myocardium-to-blood ratios, even at early times after administration. The myocardial uptake in dogs was greater than 3% at three and 15 minutes, with myocardium-to-blood ratios of about 40:1 at 15 minutes. Positron tomograms obtained with 52mMn clearly demonstrated regional myocardial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The blood T1 response of EVP-ABD was consistent with the previously observed multiexponential kinetics of Mn in blood (23,24). This confirmed that EVP-ABD behaved kinetically like free Mn in blood and explained its strong vascular enhancing capability resulting from the large molar relaxivity of Mn in blood (15,23).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The blood T1 response of EVP-ABD was consistent with the previously observed multiexponential kinetics of Mn in blood (23,24). This confirmed that EVP-ABD behaved kinetically like free Mn in blood and explained its strong vascular enhancing capability resulting from the large molar relaxivity of Mn in blood (15,23).…”
Section: Discussionsupporting
confidence: 87%
“…A previous study (22) confirmed that, as seen for Mn alone (23,24), the initial distribution of EVP-ABD from the blood was rapid. To follow such a T1 response pattern, we used a single-shot turbo-FLASH sequence at a single TI to achieve sufficient temporal resolution through the first 8 minutes post contrast injection.…”
Section: T1 Responsesupporting
confidence: 56%
“…In nuclear scintigraphic tomography, active uptake of radioactive thallium-201 ( 201 Tl) as a potassium analog (Schoeder et al 1993), and manganese 52 m ( 52m Mn) and manganese 54 ( 54 Mn) as calcium antagonists (Chauncey et al 1977;Atkins et al 1979) by viable myocytes has been applied for assessment of myocardial viability (MV). Similar approach has been adopted in cardiac MRI using cold cation Mn 2+ preparations as intracellular contrast agents for infarct imaging, since Mn 2+ is potent for T1 shortening and is taken up only in cells capable of active calcium (Ca 2+ ) transport, and thereby provides an analog to 201 Tl imaging in cardiac scintigraphy (Bremerich et al 2000;Karlsson et al 2001;Flacke et al 2003;Storey et al 2003;Krombach et al 2004).…”
Section: Intracellular Contrast Agentsmentioning
confidence: 99%
“…While in the case of Gd-compounds the SPECT nuclide 147 Gd (t 1/2 = 38.1 h, E γ = 229 keV (61%)) has been shown to be suitable [11], manganese offers two PET nuclides, namely 52m Mn (t 1/2 = 21.1 min, I β + = 97%, E β + (max) = 0.6 MeV, IT = 1.75%) and 51 Mn (t 1/2 = 46.2 min, I β + = 97%, E β + (max) = 2.5 MeV). 52m Mn of high radionuclidic purity is only available from the 52 Fe/ 52m Mn generator [12][13][14][15][16][17][18][19][20], since direct nuclear reactions, such as the 52 Cr( p, 2n) process, always lead to an isomeric mixture [3,4]. The almost pure positron emitter 51 Mn in comparison has a suitable half-life and can be produced at a small cyclotron in high radionuclidic purity using the 50 Cr(d, n) reaction [3,21].…”
Section: Introductionmentioning
confidence: 99%